Distance Differentiation in Finland : a Survey on the Experiences of English Teachers - Rantalaiho, Pinja (My University, 2021)
Differentiation and distance education have been studied quite a lot separately (see e.g. Tomlinson 2001, 2014; White 2003; Keegan 1990) but there is not much research done on the topics together: as distance differentiation. Additionally, differentiating English as a foreign language in distance education has not been studied. Also, because of the outbreak of COVID-19 in spring 2020, distance education grew rapidly in Finland and internationally. Therefore, these two topics together require more research. The aim of this study was to examine English teachers’ experiences with differentiation in distance education during spring 2020. The research questions were the following: 1) How did English teachers experience distance differentiation in spring 2020? 2) What differentiation methods did they use in distance education? The data were collected with an online questionnaire, which included both multiple-choice and open-ended questions for the purpose of qualitative and quantitative data. Basic education and general upper secondary school teachers (n=55) answered the questionnaire. The focus of this thesis was on the qualitative data that were analyzed with content analysis. Some minor statistical analysis was done on the quantitative data. The results of the study indicated that while many teachers felt like English differentiation in distance education was time-consuming, challenging, and laborious, at the same time, and at the end of the day, they viewed it quite positively by describing it as necessary and important. Teachers gave examples of their distance differentiation methods and those were divided into three main distance differentiation categories. These included 1. differentiation by task, outcome, and time allowed by offering individualized exercises usually based on the student’s level of competence in English, 2. offering individual support measures, for example remedial teaching and having personal video calls with students, and 3. students controlling their own learning and differentiation, including examples of giving the opportunity to choose from exercises on different skill levels or to substitute written exercises by completing those orally. The results showed that distance differentiation is possible and offered useful examples of distance differentiation methods for English teachers. As distance education is very likely to grow also in the future, there needs to be more research done on the topic of differentiation in that environment. Differentiation is a crucial part in making teaching fair for every student, thus it should be focused on in a distance education environment as well. As there are not many studies done on the topic of distance language differentiation, it needs to be studied more.
Keywords: differentiation, distance education, English as a foreign language, foreign language teaching, foreign language learning